Sexual Function of Primiparous Women After Elective Cesarean Section and Normal Vaginal Delivery - Hosseini, Ladan; Iran-Pour, Elham; Safarinejad, Mohammad Reza (Urology Journal, 2012)
PURPOSE: To compare sexual function between two groups of women who had normal vaginal delivery (NVD) and planned cesarean section (PCS). MATERIALS AND METHODS: In this cross-sectional study, two groups of healthy women, with antenatally normal singleton pregnancies at term, who underwent NVD (n = 114) or PCS without labor (n = 99), have been retrospectively studied. Sexual function of participants was assessed using physician-administered Female Sexual Function Index (FSFI) questionnaire before pregnancy and 6 and 24 months after delivery. Primary outcome measures were questions 3 to 6 and 14 to 16 from FSFI questionnaire. Secondary outcome measures included the remaining items. RESULTS: There were no significant differences regarding six domains of sexual function, including desire (P = .55), arousal (P = .39), lubrication (P = .45), orgasm (P = .36), pain (P = .74), and satisfaction (P = .39) between the two groups. Eighty percent of women who had undergone vaginal delivery complained from hypotonic pelvic floor muscles. CONCLUSION: We believe that PCS is not preferred to NVD in regard to preserving normal sexual functioning.